2012
DOI: 10.1371/journal.pone.0033387
|View full text |Cite
|
Sign up to set email alerts
|

Proof of Concept of Microbiome-Metabolome Analysis and Delayed Gluten Exposure on Celiac Disease Autoimmunity in Genetically At-Risk Infants

Abstract: Celiac disease (CD) is a unique autoimmune disorder in which the genetic factors (DQ2/DQ8) and the environmental trigger (gluten) are known and necessary but not sufficient for its development. Other environmental components contributing to CD are poorly understood. Studies suggest that aspects of gluten intake might influence the risk of CD occurrence and timing of its onset, i.e., the amount and quality of ingested gluten, together with the pattern of infant feeding and the age at which gluten is introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
227
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(249 citation statements)
references
References 64 publications
(84 reference statements)
6
227
0
4
Order By: Relevance
“…The ensuing dysbiosis has been associated with an increase in diseases such as asthma (8) and celiac disease (9). In addition, perinatal use of antibiotics, particularly in premature infants, can interfere with the balance of bacterial phyla and diversity of individual species and makes the newborn much more susceptible to infectious inflammatory diseases (10,11).…”
Section: Initial Colonizationmentioning
confidence: 99%
“…The ensuing dysbiosis has been associated with an increase in diseases such as asthma (8) and celiac disease (9). In addition, perinatal use of antibiotics, particularly in premature infants, can interfere with the balance of bacterial phyla and diversity of individual species and makes the newborn much more susceptible to infectious inflammatory diseases (10,11).…”
Section: Initial Colonizationmentioning
confidence: 99%
“…The most constant finding is the higher abundance of Bacteroides spp. in faeces and duodenal biopsies of CD patients (152,153,163) , although a complete lack of the members of phylum Bacteroidetes was observed in CD predisposed infants in a prospective study (149) . Furthermore, another study reported a reduction in IgA-coated bacteria, especially IgA-coated Bacteroides in faeces of untreated and treated CD patients when compared to healthy controls (151) .…”
Section: Coeliac Diseasementioning
confidence: 88%
“…A specific role for the intestinal microbiota in CD development has been suggested (149,151,152) . Indeed, deviations in faecal and duodenal microbiota associated with CD have been reported (149,(151)(152)(153) , although recent studies utilising high-throughput methods have reported comparable microbiota compositions in patients and healthy controls (154)(155)(156)(157) .…”
Section: Coeliac Diseasementioning
confidence: 99%
“…Recently, study of the human gut microbiome has been applied to CD pathogenesis (Sellito et al 2012;Cheng et al 2013;Sjöberg et al 2013). Almost a decade ago, Forsberg and colleagues (2004) In contrast, a slightly later study by Cheng and colleagues (2013) found no significant differences in the overall composition and diversity of gut microbiota (including Bacteroidetes) between a sample of 10 children with newly diagnosed CD (aged 3-14) and 9 healthy controls (aged 4-16).…”
Section: Presentation Pathophysiology and Genetics Of CDmentioning
confidence: 99%